Adaptive Reuse of Heritage Building for Youth Center with Betawi Culture - Devina, Caitlyn; Nediari, Amarena; Fajarwati, Ade Ariyani Sari (Institut Seni Indonesia Denpasar, 2025)
Colonial buildings are one type of cultural heritage building in Indonesia, with several neglected and unused buildings. Historical buildings need to be preserved to be remembered, and their architecture can be studied and maintained. It will maintain and preserve the building by adaptive reuse of historic buildings that adapt to the current conditions and environment. This research aims to apply the adaptive reuse of cultural heritage buildings into youth activity centers with a Betawi cultural interior design approach. The methodology used in this research is literature study, observation, design thinking, and location survey. The case study of adaptive reuse of cultural heritage buildings also analyzes the side effects and influences. Cultural heritage buildings are full of history and have been passed down from generation to generation. Adaptive reuse of cultural heritage buildings as a youth activity center with Betawi culture aims to become a special place to facilitate positive activities for teenagers, provide education, and preserve Betawi culture. The conclusion states that reusing cultural heritage buildings can build awareness about preserving culture and youth activity center strategies by showing positive value for society and the environment.